Breeding report of a new early-mid-maturing kiwifruit cultivar Ganjin 2 - XU Xiaobiao; HUANG Chunhui; LIAO Guanglian; ZHONG Min; JIA Dongfeng (Guoshu xuebao)
Kiwifruits belong to the family Actinidiaceae and the genus Actinidia. Among them, A. chinensis is currently the most widely cultivated species. However, cultivars of A. chinensis primarily harvest in late August to early September (the early-maturing type) or late October to early November (latematuring type). The concentration of harvest periods and the short product supply window limit the effective development of A. chinensis germplasm resources. Additionally, the inflorescences are mainly panicles, which require manual thinning of flowers and fruits to promote normal fruit development, resulting in the increase of labor costs. Therefore, medium maturity and single-flower fruiting traits are important breeding objectives for A. chinensis. Our research team conducted a detailed survey and germplasm collection of the wild kiwifruit resources in the major mountainous areas of Jiangxi Province. In Yihuang County, Jiangxi Province, we discovered a single plant with medium maturity and single-flower fruiting at an altitude of 548 m, designated YH-2. After grafting and identification, we systematically observed and evaluated its biological characteristics, key fruit traits, and genetic stability. The results from three consecutive years of trials showed that the YH-2 exhibited stable medium maturity and single-flower fruiting traits. In Fengxin County (at an altitude of 75 m), the full bloom was in mid-April, and the physiological maturity of the fruit was in late September, with the fruit development period spanning of 155-160 days. The fruit was broadly elliptical, with a single-flower fruiting rate exceeding 95%. The fruit length was 4.30 cm, the diameter was 4.25 cm, and the fruit shape index was 1.01. The fruit had a slightly blunt, convex beak, and the pedicel length was 4.30 cm. The average fruit weight was 93.60 g, the largest fruit was 127.80 g. The fruit skin was brown, covered with a moderate amount of short yellowish fuzz, while the flesh was yellow-green with distinct pith rays. The fruit quality was excellent, the soluble solid content (SSC) was 19.20%, the dry matter (DM) was 18.77%, the titratable acid (TA) was 0.98%, and the ascorbic acid (AsA) was 1.88 mg·g-1. The fruits had good storage potential and could be stored at room temperature for 30-45 days. The one-year-old branches were brownish-yellow, with an average internode length of 4.41 cm and a diameter of 0.95 cm. The fruit-bearing shoots were brown, with an average internode length of 2.36 cm and a diameter of 0.81 cm. Both the upper and lower surfaces of the young leaves and petioles were anthocyanin-colored, with pointed leaf tips and a gradually narrowing base. The mature leaves were broadly ovate with flat or slightly concave tips, measuring 9.86 cm in length and 12.19 cm in width, with petioles of 6.11 cm. The flowers were solitary or in cymose inflorescences, with 1-3 flowers per inflorescence. The petals were white, with 5-7 petals per flower. The fruiting rate of the shoots was high (91.5%), and the plant exhibited strong continuous fruiting ability, with normal vegetative branches becoming fruiting shoots in the following year. The fruit setting rate exceeds 95%, and flower and fruit drop were very low. The fruit matured in late September. The yield during the full fruit-bearing period was 28.50 t·hm-2.